Comparison of Bimatoprost and Timolol for Treatment of Chronic Angle Closure Glaucoma: Bimatoprost Versus Timolol in Chronic Glaucoma - Ali, Zulfiqar; Nazir, Nadia; Farrukh, Soufia; Khalid, Muhammad; Mukhtar, Sarfraz Ahmad; Khan, Muhammad Jahanzaib (Pakistan Journal of Health Sciences, 2024)
Angle-closure glaucoma occurs when the normal drainage of fluid within the eye, specifically the aqueous humor, is obstructed or restricted. Objective: To assess and compare bimatoprost 0.03% administered once daily versus timolol 0.5% administered twice daily in patients diagnosed with chronic angle closure glaucoma (CACG). Methods: This randomized controlled study was performed at the Department of Ophthalmology, Bahawalpur Victoria Hospital, Bahawalpur, Pakistan, from August 2023 to January 2024. Patients of either gender, aged 18 years or older, and diagnosed with unilateral or bilateral CACG were included. Patients were randomly allocated to either Bimatoprost 0.03% (once daily at night) or Timolol malete 0.5% (two times morning and night daily) adopting a lottery method. Patients were asked to visit after one and 3 months (final outcome) and intraocular pressure (IOP) measurements were taken between 8 to 10 am using an applanation tonometer. Results: A total of 110 patients of which 64 (58.2%) were female. The mean age was 58.9 ± 10.5 years. At baseline, the mean intraocular pressure was calculated to be 24.2 ± 5.7 mmHg. After 1-month (18.7 ± 4.2 mmHg vs. 20.5 ± 4.7 mmHg, p=0.0418) and 3-months of treatment (16.8±4.6 mmHg vs. 19.6 ± 4.3 mmHg, p=0.0030), the mean IOP were significantly less in Bimatoprost group when compared to Timolol group. The commonest adverse events were conjunctival hyperaemia, and pruritus reported by 19 (17.3%), and 9 (8.2%) patients respectively. Conclusions: Bimatoprost exhibited a significantly better reduction in IOP compared to timolol in chronic angle closure glaucoma. Both drugs showed relatively good safety and tolerability profiles.